2022
DOI: 10.3389/fendo.2022.1008275
|View full text |Cite
|
Sign up to set email alerts
|

Association between caffeine intake and lumbar spine bone mineral density in adults aged 20–49: A cross-sectional study

Abstract: BackgroundMany epidemiological studies have investigated the connection between coffee intake and bone mineral density (BMD), but the results are controversial. This study aimed to assess the association between caffeine consumption and lumbar BMD in adults aged 20–49.MethodsFrom a cross-sectional study based on a large sample of the National Health and Nutrition Examination Survey 2011–2018. After controlling for confounders, the weighted multivariate linear regression model was created and stratified by age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…As life expectancy has increased, there has been a rise in the prevalence of osteoporosis, leading to a decline in quality of life and an increase in medical expenses. Apart from genetic factors, age, and lifestyle choices [ 3 , 4 ], such as lipid or glucose metabolism [ 5 7 ], have recently drawn considerable attention due to their influence on bone metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…As life expectancy has increased, there has been a rise in the prevalence of osteoporosis, leading to a decline in quality of life and an increase in medical expenses. Apart from genetic factors, age, and lifestyle choices [ 3 , 4 ], such as lipid or glucose metabolism [ 5 7 ], have recently drawn considerable attention due to their influence on bone metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…In a clinical study of Korean postmenopausal women (n=4066), using multivariate logistic regression analysis to adjust for confounders, the prevalence of osteoporosis was found to be 36% lower in a cohort with 2-3 times per day coffee intake (n=998) compared with a cohort with less than 1 time per month (n=872) ( 9 ). Besides, the results of another recent cross-sectional study including 7041 U.S. adults (between the ages of 20-49 years) showed that higher coffee intake was significantly and positively associated with LS-BMD (between the ages of 30-39 years) in women ( 34 ). In addition, studies from New Zealand, Hong Kong, and Taiwan have produced similar results ( 6 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Rapuri et al [ 18 ] proved that caffeine could impair osteoblast activation by reducing the vitamin D receptor expression on human osteoblasts and alkaline phosphatase activity. However, clinical research has always drawn inconsistent conclusions with different populations, study designs, or doses of caffeine intake [ 13 , 19 , 20 ]. A recent study of the National Health and Nutrition Examination Survey (NHANES) by Wang et al [ 19 ] indicated caffeine could increase lumbar spine BMD in women aged 30–39 but could have a negative effect on men aged 40–49.…”
Section: Introductionmentioning
confidence: 99%